Implementation of Digital Marketing and Packaging Assistance to The Tista Tourism Village MSME Group - Tabita, I Dewa Ayu Tita Permata; Luh Gede Putri Kusuma Pekerti; Made Christin Dwitrayani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The Tista Tourism Village MSME group has various business activities under the auspices of the Sari Merta Village-Owned Enterprise (Bumdes). One of the businesses that many local people are involved in is processing agricultural products. Things that become obstacles for MSMEs are product packaging and digital marketing, which causes a lack of product orders because they only rely on marketing in rural areas. This community service aims to provide knowledge about digitalization in the marketing sector so that it can reach potential buyers from outside the village and how to create attractive packaging to attract customers, thereby increasing product sales. The method used is to explain how important it is to sell online and practice the system using the Instagram, Shopee, and Tokopedia applications. And, for the packaging sector, training is provided on how to design product packaging and logos using the Canva application. This community service concludes that there has been an increase in sales of MSME products; this is based on the results of a questionnaire that has been given to the group, where the Tista Tourism Village MSME group has been able to market its products through digital applications.